SARS-CoV-2 Spike Protein-Directed Monoclonal Antibodies May Ameliorate COVID-19 Complications in APECED Patients - Ferré, Elise M. N.; Schmitt, Monica M.; Ochoa, Sebastian; Rosen, Lindsey B.; Shaw, Elana R.; Burbelo, Peter D.; Stoddard, Jennifer L.; Rampertaap, Shakuntala; DiMaggio, Tom; Bergerson, Jenna R. E.; Rosenzweig, Sergio D.; Notarangelo, Luigi D.; et al. (Frontiers in Immunology, 2021)
Patients with the monogenic immune dysregulatory syndrome autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED), which is caused by loss-of-function mutations in the autoimmune regulator (AIRE) gene, uniformly carry neutralizing autoantibodies directed against type-I interferons (IFNs) and many develop autoimmune pneumonitis, both of which place them at high risk for life-threatening COVID-19 pneumonia. Bamlanivimab and etesevimab are monoclonal antibodies (mAbs) that target the SARS-CoV-2 spike protein and block entry of SARS-CoV-2 in host cells. The use of bamlanivimab and etesevimab early during infection was associated with reduced COVID-19–associated hospitalization and death in patients at high risk for progressing to severe disease, which led the US Food and Drug Administration to issue an emergency use authorization for their administration in non-hypoxemic, non-hospitalized high-risk patients. However, the safety and efficacy of these mAbs has not been evaluated in APECED patients. We enrolled two siblings with APECED on an IRB-approved protocol (NCT01386437) and admitted them prophylactically at the NIH Clinical Center for evaluation of mild-to-moderate COVID-19. We assessed the safety and clinical effects of early treatment with bamlanivimab and etesevimab. The administration of bamlanivimab and etesevimab was well tolerated and was associated with amelioration of COVID-19 symptoms and prevention of invasive ventilatory support, admission to the intensive care, and death in both patients without affecting the production of antibodies to the nucleocapsid protein of SARS-CoV-2. If given early in the course of COVID-19 infection, bamlanivimab and etesevimab may be beneficial in APECED and other high-risk patients with neutralizing autoantibodies directed against type-I IFNs.